General equilibrium long-run determinants for Spanish FDI: A spatial panel data approach - Jaime Martínez-Martín (SERIEs - Journal of the Spanish Economic Association, 2011)
While general equilibrium theories of trade stress the role of third-country effects, little work has been done in the empirical foreign direct investment (FDI) literature to test such spatial linkages. This paper aims to provide further insights into long-run determinants of Spanish FDI by considering not only bilateral but also spatially weighted third-country determinants. The few studies carried out so far have focused on FDI flows in a limited number of countries. However, Spanish FDI outflows have risen dramatically since 1995 and today account for a substantial part of global FDI. Therefore, we estimate recently developed spatial panel data models by maximum likelihood (ML) procedures for Spanish outflows (19932004) to top-50 host countries. After controlling for unobservable effects, we find that spatial interdependence matters and provide evidence consistent with new economic geography theories of agglomeration, mainly due to complex (vertical) FDI motivations. Spatial error models estimations also provide illuminating results regarding the transmission mechanism of shocks.
Keywords: F21; F23; C31; C33; 330; foreign direct investment; spatial econometrics; panel data; Direktinvestition; Allgemeines Gleichgewicht; Maximum-Likelihood-Methode; Schätzung; Spanien